MODERN SEDIMENTOGENESIS OF THE AZOV SEA: FACTORS AND FEATURES - T.M. Alokhina; L.V. Kurazieva; V.V. Skvortsov (Геологія і корисні копалини Світового океану, 2019)
The process of sedimentation in the region of the northern coast of the Azov Sea is characterized by significant changeability of parameters. In the formation of modern sediments the relation of biogenic processes, riverine load, coastal abrasion and eolic deposition is played an important role in conditions of constant increase of technogenic and anthropogenic factors.